Lachiri v Belgium: Application no 3413/09: European Court of Human Rights (Second Section): Spano, President, Lemmens, Karakaş, and Kjølbro JJ; Vučinić and Griţco JJ concurring; Mourou-Vikström J dissenting: 18 September 2018. (13th November 2018) - Paul, Kaushik
Abstract: Human rights – Freedom of religion or belief – Manifestation of religion by wearing religious garment – Interference with – Applicant hijab-wearing devout Muslim woman – Applying to join criminal proceedings as civil party in order to seek damages – In accordance with decision of presiding judge, court usher telling the applicant to remove her hijab before entering courtroom – Applicant refusing and not attending hearing – Applicant unsuccessfully challenging decision – Whether exclusion of the applicant from the courtroom on the sole ground that she refused to remove her hijab constituted a restriction of her right to manifest her religion – Whether interference prescribed by law – Whether pursued a legitimate aim – Whether necessary in a democratic society – European Convention on Human Rights, art 9